Annotated list of the Euchromiina “wasp moths” (Lepidoptera: Erebidae: Arctiinae: Arctiini) from the department of Loreto (Peru), with the report of new records and synonyms - Grados, Juan (2021)
For the department of Loreto, 113 species of Euchromiina (Lepidoptera: Arctiinae) are recorded. In addition, 9 new records are reported for Peru: Sphecosoma abnormis, Isanthrene profusa, Autochloris collocata, A. consociata, Andrenimorpha lycopolis, Leucotmemis torrida, Cosmosoma contracta, Pseudomya biradiata and P. cretheis. Two new synonyms are proposed: Diptilon aurantiipes Rothschild as a junior synonym for Sphecosoma abnormis Hampson; Isanthrene flavizonata Gaede as a junior synonym for Tigrinadia quadricincta Kaye. This last species for now is known only from Peru. A new type of androconial organ is described in the ventral part of the abdomen.